Statistical Analysis of Key Criteria Identifying Corporate Cultures - Liliia V. Matraeva; Alexey A. Konov; Sergey G. Erokhin (International Review of Management and Marketing, 2016)
The aim of this article is to revise main distinctions between corporate cultures of different nations. National corporate cultures have long been a point of interest for economists around the world. The question remains important nowadays as well, and will be so in future, since effective cross-border cooperation is one of the crucial factors, allowing attracting overseas investors. Modern researches have proven that both cultural and financial cross-national bonds are getting stronger these days, which leads to creating new paradigms of international cooperation across the globe. Author creates new methods, allowing analysing cross-cultural variance and statistically forecasting how effective will intercultural interaction be. These methods are then implemented to assess transnational cooperation and identify its specific traits on the example of Russia and its economical partners – countries that create the most of direct investments in Russian economy.